Dating the Holocene Incision of the Danube in Southern Hungary - Tóth, Orsolya; Sipos, György; Kiss, Tímea; Bartyik, Tamás (Journal of Environmental Geography, 2017)
The alluvial development of the Great Hungarian Plain has greatly been determined by the subsidence of different areas in the Pannonian Basin. The temporal variation of subsidence rates significantly contributed to the avulsion and shifting of main rivers. This was the case in terms of the Hungarian Lower Danube when occupying its present day N-S directional course. The considerable role of tectonic forcing is also supported by the presence of different floodplain levels. Although, several channel forms are identifiable on these the timing of floodplain development has been reconstructed up till now mostly by the means of geomorphological analysis, and hardly any numerical dates were available. The main aim of this study is to provide the first OSL dates for palaeo-channels located on the high floodplain surface of the Hungarian Lower Danube, and to determine the maximum age of low and high floodplain separation on the Kalocsa Plain. For the analysis two meanders were sampled close to the edge of the step slope between the two levels. According to the results, the development of the investigated palaeo-meanders could be rapid. The formation of the older meander was dated to the Late Atlantic, while the possible separation of the high and low floodplain surfaces could start in the beginning of the Subboreal Phase.